Strategi Implementasi Diagnosis, Intervensi dan Luaran Keperawatan Indonesia terhadap Perawat - Umboh Morenita Jeanifer; Ati Surya Mediawati; Irman Somantri (Journal of Telenursing (JOTING), 2023)
This study explores strategies for implementing Indonesian nursing diagnoses, interventions, and outcomes for hospital nurses. This research method uses a scoping review approach. The research results found 12 articles that describe seven main components of strategies for implementing standard diagnosis, intervention, and outcomes of Indonesian nursing, namely educational programs, case study discussions, assistance using instruments, observation, innovation, role play, and demonstration. Conclusion The strategy for implementing training, case study discussions, and service using devices, words, innovation, role play, and demonstrations can increase nurses' knowledge and skills in nursing practice and patient safety using Indonesian hospital nursing standards. Keywords: Indonesia, Nurses, SDKI SLKI SIKI, Standardization